PENERAPAN MODEL LEARNING CYCLE KARPLUS UNTUK MENINGKATKAN PROBLEM SOLVING SKILLS DAN HASIL BELAJAR IPA KELAS V SD NEGERI 2 PADOKAN - Adinugroho, Muhamad Wahyu; Sujatmika, Sigit; Rezkita, Shanta (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to improve problem-solving skills and learning achievement by applying the Karplus Learning Cycle Model on students of class VC of SD N 2 Padokan Bantul, totaling 20 students. This research was a classroom action research and was carried out in two cycles.  Data collection techniques were test and non-test. Students? problem-solving skills data were collected using pretest and posttest as well as observation sheets, while science learning achievement of students was taken using pretest and posttest. The data were analyzed using descriptive analysis techniques. The results showed that problem-solving skills and learning achievements of the students in class VC SD N 2 Padokan can be improved through learning with the Karplus Learning Cycle Model. Each stage of the Karplus Learning Cycle Model can improve aspects of problem-solving skills and student learning achievement. The Exploration stage increases the aspect of understanding the problem. The Explanation phase enhances the aspects of planning a solution. The concept application stage improves aspects of solving problems and evaluating problem-solving. Improved problem-solving skills are proven through test results, where the average N gain of class in the first cycle was 0.37 with the moderate category, up to 0.70 with the high category in the second cycle.  This is also strengthened from the results of observations, where the average scores of the class increase from the first cycle of 67.61% with a pretty good category to 91.66% with a very good category in the second cycle.  The increase in student learning achievements is evidenced through the results of the test, where an increase in the number of students who reached KKM 75 from the first cycle as much as 90% to 100% in the second cycle.